NATO strategy for 2010 and its implications for the Arab world - Abdullah, Enas Ahmed (Journal of Economic, Administrative and Legal Sciences, 2025)
The North Atlantic Treaty Organization (NATO), initially created to contain communist expansion during the Cold War, continued to evolve and adapt after the demise of the Soviet Union in 1991, expanding to include Eastern European and Baltic states to counter growing Russian influence. Despite its shift from confronting the communist threat to confronting contemporary challenges such as terrorism and illegal immigration, the Alliance has played an influential military role in multiple regions, including the first intervention outside its geographical scope after the attacks of September 11, 2001. With the rise of new global powers such as Russia and China, NATO continues to strengthen its defense capabilities and modernize its strategies, increasingly focusing on the Middle Eastern region because of its strategic importance and energy resources, especially after the Ukrainian crisis and Russia’s annexation of the Crimean Peninsula in 2014, which makes its continuity and development necessary to preserve On the global strategic in balance.
Keywords: NATO; terrorism; member states; piracy; war; interventions; agreements